Use of Ar pellet ablation rate to estimate initial runaway electron seed population in DIII-D rapid shutdown experiments. (3rd October 2016) - Hollmann, E.M.; Commaux, N.; Moyer, R.A.; Parks, P.B.; Austin, M.E.; Bykov, I.; Cooper, C.; Eidietis, N.W.; O'Mullane, M.; Paz-Soldan, C.; Rudakov, D.L.; Shiraki, D.
Abstract: Small (2–3 mm, 0.9–2 Pa · m 3 ) argon pellets are used in the DIII-D tokamak to cause rapid shutdown (disruption) of discharges. The Ar pellet ablation is typically found to be much larger than expected from the thermal plasma electron temperature alone; the additional ablation is interpreted as being due to non-thermal runaway electrons (REs) formed during the pellet-induced temperature collapse. Simple estimates of the RE seed current using the enhanced ablation rate give values of order 1–10 kA, roughly consistent with estimates based on avalanche theory. Analytic estimates of the RE seed current based on the Dreicer formula tend to significantly underestimate it, while estimates based on the hot tail model significantly overestimate it.